2021
DOI: 10.36660/abc.20200547
|View full text |Cite
|
Sign up to set email alerts
|

Aumento de Óbitos Domiciliares devido a Parada Cardiorrespiratória em Tempos de Pandemia de COVID-19

Abstract: Resumo Fundamento As doenças cardiovasculares constituem um grupo importante de causas de morte no Brasil. As doenças isquêmicas do coração são as principais causas de parada cardiorrespiratória, levando a um impacto na mortalidade devido às doenças cardiovasculares no sistema de saúde. Objetivo Avaliar o número de óbitos domiciliares por parada cardiorrespiratória notificados pelo Serviço de Atendimento Móvel de Urgência (SAMU) em março de 2018, 2019 e 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 13 publications
1
2
0
2
Order By: Relevance
“…First, studies revealed a reduction in hospitalizations, procedures, and/or consultations for CVD in high, [26][27][28][29][30] and low-and middle income countries (LMIC), 31,32 then an increase in out-of-hospital deaths. 33,34 Moreover, a rise in the proportion of inhospital mortality for CVD was reported, being this effect larger where greater decline in admission rates occurred, suggesting hospitalizations of sicker patients or delivery of worse quality of care, corroborating our findings. 35,36 In parallel, other studies revealed that excess mortality in the pandemic period could not be explained exclusively by COVID-19 deaths, and excess CVD deaths was found in some countries, including Brazil, which is not surprising, knowing the beneficial effect of in-hospital timely treatment for the most lethal cardiovascular conditions, such as ACS.…”
Section: Discussionsupporting
confidence: 88%
“…First, studies revealed a reduction in hospitalizations, procedures, and/or consultations for CVD in high, [26][27][28][29][30] and low-and middle income countries (LMIC), 31,32 then an increase in out-of-hospital deaths. 33,34 Moreover, a rise in the proportion of inhospital mortality for CVD was reported, being this effect larger where greater decline in admission rates occurred, suggesting hospitalizations of sicker patients or delivery of worse quality of care, corroborating our findings. 35,36 In parallel, other studies revealed that excess mortality in the pandemic period could not be explained exclusively by COVID-19 deaths, and excess CVD deaths was found in some countries, including Brazil, which is not surprising, knowing the beneficial effect of in-hospital timely treatment for the most lethal cardiovascular conditions, such as ACS.…”
Section: Discussionsupporting
confidence: 88%
“…De fato, artigo publicado nos Arquivos Brasileiros de Cardiologia em 2020 20 relatou um aumento no número de óbitos por parada cardiorrespiratória no Brasil apresentando como comorbidade clínica hipertensão arterial sistêmica para 22% dos casos investigados pela pesquisa. Este padrão de mortalidade provavelmente indica que pessoas portadoras de hipertensão arterial e outras doenças cardiovasculares deixaram de demandar os serviços de saúde em função da COVID-19, seja pela superlotação dos serviços, seja por medo de contrair o Sars-Cov2.…”
Section: Discussionunclassified
“…This discrepancy stems from cases in which COVID-19 was not suspected but the RT-PCR results were positive, as seen mainly in deaths from cardiovascular diseases (32.43% were COVID-19 positive). What may initially seem to be an excess of non-suspected COVID-19 deaths resulted only from the difficulty of individuals to access health services 25 , and, after obtaining the RT-PCR results, we identified COVID-19-related deaths with atypical/asymptomatic clinical presentations, lacking criteria for suspicion. This suggests that the patient died of a cause other than COVID-19 infection, although the infection was detected.…”
Section: Discussionmentioning
confidence: 99%